Pelatihan Bahasa Arab Dasar Menggunakan Metode Tat’biq Pada Mahasiswa PAI Universitas Negeri Padang - Amanah, Tegu Reski; Martin Kustati; Gusmirawati (STKIP Andi Matappa, 2024)
Arabic is a scientific tool to support understanding and deriving meaning from the propositions in the form of the Koran and Hadith which are standard in Arabic form. The purpose of studying Arabic is an important and useful way to understand it, especially for someone who has a religious focus, such as Islamic-based schools such as Islamic boarding schools, madrasas, Integrated Islamic schools, or Islamic-based tertiary institutions, as well as non-formal learning such as halaqoh. and Islamic teachings, so that learning cannot be separated from the Koran, Hadith and books written by ulama. The methods used by each educational institution are different, one of the methods used in learning Arabic is the Muhadharah method. The Muhadharah method in non-formal Arabic language learning takes the form of practical learning which is carried out in the form of delivering material and interaction in the form of discussions, generally focusing more on developing speaking and communication skills. In the context of Arabic language training using the Muhadharah method at student level, the delivery of material is usually carried out contextually and integrated with reading, listening and speaking practice.